FRI0406 AQUILA STUDY IN GERMANY – REAL WORLD DATA ON SECUKINUMAB'S EFFECTIVENESS IN ANKYLOSING SPONDYLITIS PATIENTS – RESULTS FROM AN INTERIM ANALYSIS. (June 2019) - Kiltz, Uta; Peterlik, Daniel; Winkelmann, Veronika; Tony, Hans-Peter; ,
Abstract : Background: Ankylosing spondylitis (AS) is characterized by chronic inflammation of the spine and is at high risk to cause inflammation, pain, and stiffness extraspinal as well. Thus, important aims in therapy of AS are pain reduction and maintenance of physical functioning. Secukinumab, a fully human monoclonal antibody that selectively neutralizes interleukin (IL)-17A, has already shown significant efficacy in the treatment of AS in clinical trails 1 . Objectives: The aim of this interim analysis is to evaluate the effectiveness of secukinumab on disease activity, physical functioning and quality of life in AS patients (pts) in a real world setting. Methods: AQUILA is an ongoing, multi-center, 52-week (wk) non-interventional study enrolling 2000 pts with active AS and psoriatic arthritis in Germany. Here, we report interim results of effectiveness in a subgroup of AS pts treated with secukinumab. Validated questionnaires were used to measure the effectiveness of secukinumab on: disease activity Physician's Global Assessment (PhGA: 0=no disease activity, 10=most intense disease activity), Bath Ankylosing Disease Activity Index (BASDAI), C–reactive protein (CRP) physical functioning global functioning: Assessment of Spondyloarthritis Health Index, (ASAS–HI), and key aspects of sleep Medical outcomes Study Sleep Scale (MOS), severity of depression Beck's Depression Inventory Version II (BDI–II). Pts who were already under secukinumab treatment or just about initiating secukinumab therapy, based on medical therapeutic need, were included; in both scenarios, disease activity at start of secukinumab treatment was used as starting point for analysis. Treatment decision was made independently of participating in this study. Pts were observed from BL up to wk 52 according to clinical routine. Real-world effectiveness of secukinumab was assessed prospectively and analyzed as observed. Results: This interim analysis describes 311 AS pts who were included at BL and of whom 178 (57.2%) have completed wk 52 so far (i.e. at the time of data cut-off for this interim analysis). 63.3% (n=197) of the pts were male and 36.7% (n=114) female, mean age was 47 years. About 70% (n=221) of the pts were pre-treated with biologics. Physicians reported a mean PhGA value of 5.9 at BL (n=282, 90.7%) which improved to 2.6 at wk 52 (n=168, 54.0%). Mean BASDAI value was reduced from 5.6 at BL (n=301, 96.8%) to 4.0 at wk 52 (n=171, 55.0%). With regard to inflammation parameters, the percentage of pts with a CRP of >5mg/L decreased from 54.7% (n=140) to 40.0% (n=58) at wk 52. Further, mean ASAS-HI value decreased over time from 8.2 at BL (n=274, 88.1%) to 6.3 at wk 52 (n=156, 50.2%). MOS sleep scale did not change over time, yet only few BL documentations for these scales were available (range n=26 to 44). Regarding depressive mood of the pts, while at BL 40.7% (n=101) of the pts suffered from mild to severe depression (BDI-II score between 14 and 63), 30.3% (n=46) did so in wk 52. This is reflected by a drop of mean BDI-II value from 13.0 at BL (n=248, 79.7%) to 10.6 at wk 52 (n=152, 48.9%). Conclusion: Within this limited subset of AS pts, secukinumab reduced disease activity and improved quality of life for up to one year as assessed by validated physicians' as well as pt-reported outcomes. Overall, this interim analysis gives promising insights into treatment effects of secukinumab on pts' physical and mental well-being under real-world conditions. References: [1] Baeten D, et al. N Engl J Med. 2015;373:2534-4 Disclosure of Interests: Uta Kiltz Grant/research support from: AbbVie, Chugai, Eli Lilly, Grünenthal, Janssen, MSD, Novartis, Pfizer, Roche, and UCB., Consultant for: AbbVie, Chugai, Eli Lilly, Grünenthal, Janssen, MSD, Novartis, Pfizer, Roche, and UCB., Daniel Peterlik Employee of: Novartis Pharma GmbH, Veronika Winkelmann Employee of: Novartis Pharma GmbH, Hans-Peter Tony Consultant for: Eli Lilly and Company, Speakers bureau: Eli Lilly and Company